Інтеграція житла для мігранта у громадські та промислові об’єкти - Баб’як, В. І.; Babyak, V. (Видавництво Львівської політехніки, 2017)
У статті розглянуто передумови створення і формування різних типів житла для мігрантів, а також чинників, котрі впливають на формування житла для мігрантів у структурі житлової забудови. На основі перелічених чинників запропоновано моделі архітектурно-планувальних вирішень і варіанти їхньої інтеграції у житлове середовище.

The article examines the problems of development and implementation in Ukraine types of housing for migrants integrated into the structure of the residential area. Based on the analysis international and domestic experience in the models of housing that can be adapted to the needs of housing for migrants. The work considers prerequisites for development and formation of different types of housing for migrants as well as factors - which influence the formation of housing for workers within the structure of residential development. Based on these factors the models of architectural and planning solutions and options for their integration into the living environment.
Integration of housing for migrants into public and industrial facilities
Keywords: житло для мігрантів; типи житла; ґеттоїзація; інтеграція у суспільство; housing for migrants; types of housing; he emergence of ghettos; integration into society; 728